2020
DOI: 10.1080/10799893.2020.1825492
|View full text |Cite
|
Sign up to set email alerts
|

MiR-33a-5p targets NOMO1 to modulate human cardiomyocyte progenitor cells proliferation and differentiation and apoptosis

Abstract: Purpose: MicroRNA (miRNA) is known to be involved in the pathological process of congenital heart disease (CHD), and nodal modulator1 (NOMO1) is a critical determinant of heart formation. The present study aims to discover the effect of miR-33a-5p and NOMO1 on CHD. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was used to detect expressions of miR-33a-5p mimic or inhibitor and overexpressed NOMO1 plasmid orNOMO1 knockdown. Human cardiomyocyte progenitor cells (hCMPCs) proliferation was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…MiRNA-33a-5p is an intron miRNA that is located inside the intron sequence of the sterol-response-element-binding protein gene 2 (SREBP2) ( 63 ). The study has shown that miR-33a-5p promotes apoptosis via targeting nodal modulator1 (NOMO1) and other targets ( 64 ). After treatment with Hcy in the CMEC vascular dysfunction model, growth-arrest specific transcript 5 (GAS5) expression is markedly reduced whereas miRNA-33a-5p expression is elevated ( 65 ).…”
Section: Role Of Mirna In Cmec In Cardiovascular Diseasementioning
confidence: 99%
“…MiRNA-33a-5p is an intron miRNA that is located inside the intron sequence of the sterol-response-element-binding protein gene 2 (SREBP2) ( 63 ). The study has shown that miR-33a-5p promotes apoptosis via targeting nodal modulator1 (NOMO1) and other targets ( 64 ). After treatment with Hcy in the CMEC vascular dysfunction model, growth-arrest specific transcript 5 (GAS5) expression is markedly reduced whereas miRNA-33a-5p expression is elevated ( 65 ).…”
Section: Role Of Mirna In Cmec In Cardiovascular Diseasementioning
confidence: 99%
“…Abundant literature has confirmed the crucial role of miRNAs in the pathogenesis of human cancers, including breast cancer 9–11 . By targeting different molecules, miRNAs are capable to regulate various biological processes, including cell proliferation and apoptosis 12,13 . Research has disclosed the inhibitory effect of miR‐1283 in mediating cell proliferation and the facilitating role in the regulation of cell apoptosis in glioma and liver cancer 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] By targeting different molecules, miRNAs are capable to regulate various biological processes, including cell proliferation and apoptosis. 12,13 Research has disclosed the inhibitory effect of miR-1283 in mediating cell proliferation and the facilitating role in the regulation of cell apoptosis in glioma and liver cancer. 14,15 However, to our knowledge, the exact impact of miR-1283 on HER2+ breast cancer remains poorly understood.…”
mentioning
confidence: 99%
“…Conversely, other pathways appear to be regulated only by pro-proliferative or pro-apoptotic miRNAs, such as the NF-kB pathway which can be activated by blockade of the suppressor of cytokine signaling 3 (SOCS3) and the NF-kB inhibitor interacting Ras-like 2 (NKIRAS2) by miR-324 [38] and miR-1180 [39], respectively. However, the Nodal signaling pathway, an important signal transduction pathway active during embryonic heart development [40], is suppressed by miR-33a-5p which targets nodal modulator 1 (NOMO1) [41].…”
Section: Introductionmentioning
confidence: 99%
“…92, miR-19a/b or miR-221-3p [33][34][35] or silenced by miR-208a and miR-489, which b phosphoinositide 3-kinase (PI3K) and spindlin-1 (SPIN1), respectively [36 Conversely, other pathways appear to be regulated only by pro-proliferative or apoptotic miRNAs, such as the NF-kB pathway which can be activated by blockade o suppressor of cytokine signaling 3 (SOCS3) and the NF-kB inhibitor interacting Ras-l (NKIRAS2) by miR-324 [38] and miR-1180 [39], respectively. However, the Nodal sig ing pathway, an important signal transduction pathway active during embryonic h development [40], is suppressed by miR-33a-5p which targets nodal modulat (NOMO1) [41]. 92, miR-19a/b or miR-221-3p [33][34][35] or silenced by miR-208a and miR-489, which b phosphoinositide 3-kinase (PI3K) and spindlin-1 (SPIN1), respectively [36 Conversely, other pathways appear to be regulated only by pro-proliferative or apoptotic miRNAs, such as the NF-kB pathway which can be activated by blockade of suppressor of cytokine signaling 3 (SOCS3) and the NF-kB inhibitor interacting Ras-li (NKIRAS2) by miR-324 [38] and miR-1180 [39], respectively.…”
Section: Introductionmentioning
confidence: 99%